Where periodontitis meets metabolic syndrome—The role of common health‐related risk factors. (25th April 2019) - Abdalla‐Aslan, Ragda; Findler, Mordechai; Levin, Liran; Zini, Avraham; Shay, Boaz; Twig, Gilad; Almoznino, Galit
Abstract: Objectives: To analyse and compare associations between metabolic syndrome (MetS) and its components in periodontitis compared to control patients. Methods: This 7‐year cross‐sectional study retrospectively analysed medical records of 504 individuals aged 18‐90 who attended the student dental clinic between 2008 and 2014. Demographics, smoking habits, blood pressure, waist circumference, as well as presence of: periodontitis, MetS, diabetes, hypertension, hyperlipidaemia, stroke, heart disease, cancer and psychiatric disorders were recorded. Results: The study population composed of 231 (45.8%) males and 273 (54.2%) females, with an average age of 55.79 ± 16.91 years. A patient profile associated with periodontitis was identified and included male sex, older age, smoking, higher smoking pack‐years, abdominal obesity, higher systolic and diastolic blood pressures, the presence of MetS or its components, hypertension, hyperlipidaemia, diabetes or diseases associated with its consequences such as ischaemic heart disease and stroke. Following multivariate logistic regression analysis, age and smoking retained a significant association with periodontitis, whereas the systemic disorders did not. Conclusions: The association between periodontitis and MetS may be explained by shared common profile and risk factors. An appropriate risk factors management approach should be adopted by both dental and general health clinicians and health authorities, to control common high‐risk behaviours.